Effects of transient slamming and harmonic swings on the marine compound NC machine tool. (1st November 2015) - Sun, Yewang; Zhang, Zhijing; Zhang, Jiaying; Jin, Xin; Xu, Binshi; Deng, Yongjun; Zhao, Gang
Abstract: To study structural seakeeping stability of the marine compound NC machine tool in the ship environment, this research analyses the effects of extreme wave loads including transient slamming and harmonic swings on the machine tool, and the coupling methods of transient reaction, static structural analysis and harmonic response are used to solve the problems. The results show that the major guide pairs of the column are the weakest parts in the machine tool in a ship environment, so the column working deflection angle of the machine tool should be consistent with the ship heading angle to reduce influence of wave loads on dynamic stability of the machine. The data indicate that the minimum safety factor is 3.43 under an extreme surge acceleration of 41.8 m/s 2, and the normal safety factor of 3.0 shows that the guide pairs are able to endure extreme slamming wave loads of H 1/3 =7.6 m at the maximum velocity of the ship. In addition, the machine tool has a maximum deformation of 0.032 mm and a peak stress of 5.07 MPa under extreme harmonic wave excitation. Importantly, the machine's cutting accuracy was suitable for the rapid manufacturing requirement to maintain a ship's broken components. Highlights: The extreme wave acceleration loading method is presented. The coupling method of transient and static structural analysis is proposed. The guide-slider AHP model and numerical tolerance model are presented. The macro–micro vibration mathematical model of the machine tool are proposed. The coupling method of experimental and FEM modal analysis is presented.